Analisis Fraud Diamond Dalam Mendeteksi Financial Statement Fraud - Risa Nadila Agustina; Yulinartati; Nina Mariana (LPPM POLITEKNIK LP3I BANDUNG, 2023)
This study aims to determine the potential for fraudulent financial statements by using fraud analysis, where fraud is a concept that explains the factors that cause someone to commit fraud, namely opportunity, pressure, rationalization and ability. Opportunity factor is proxied by using financial stability and external pressure. The opportunity factor is proxied by using industrial properties and control effectiveness. The rationalization factor is proxied by rationality and auditor turnover. Finally, the ability factor is proxied by ability. This study uses the F_Score indicator to see the potential for fraudulent financial statements. The population of this study consisted of 193 companies, with 15 samples of companies. The sampling technique used was purposive sampling. Collecting data using secondary data. Data analysis using multiple linear regression analysis method. The results showed that partially (t test) financial stability and external pressure variables had a effect on the potential for fraudulent financial statements. Meanwhile, the nature of industry, change in auditor, and capability variables have no effect on the potential for fraudulent financial statements.